P2.074 Comparison of Specimen Type For the Diagnosis of TrichomonasVaginalis (TV) Using the Viper TM System is Extracted Mode. (13th July 2013) - Schwebke, J R; Fuller, D; Taylor, S; Lebed, J; Smith, B; Pol, B Van Der; Nye, M; Rivers, C; Aycock, C; Gaydos, C
Abstract : Background: TV is the most common curable STI worldwide and is associated with adverse consequences including preterm birth and acquisition/transmission of HIV. Yet, until recently, testing options for this infection were limited and had suboptimal sensitivity. Recently, nucleic acid amplification test systems (NAATS) for diagnosis of TV have been developed. Various types of specimens were studied in this process. We now report on the agreement of these specimen types for the diagnosis of TV using this NAATS assay. Methods: Eight centres participated in this study. Specimens were collected from subjects presenting with symptoms of trichomoniasis or for routine visits. Specimens were collected in the following order: (1) first void urine, (2) patient-collected vaginal swab, (3) three clinician-collected vaginal swabs, (4) endocervical swab. Urine was aliquotted into a Viper neat and UPT tube for BD ProbeTec™ Trichomonas vaginalis (TV) Q x Amplified DNA Assay (TVQ) testing. The three clinician-collected vaginal swabs were used for wet mount, culture, and comparator testing. Sensitivity and specificity for the specimen types were calculated by comparing results to the patient infected status (PIS) algorithm of wet mount and TV culture. Results: Results from 838 participants were available for evaluation. The overall prevalence of TV in this population was 120/838 (14.3%). Using the self-collected vaginal swab as the reference comparator, there was excellent agreement between vaginal swabs, neat and UPT urine, and endocervical swabs (kappa 0.93–0.95). Of these specimen types, endocervical had the lowest yield but still had excellent agreement with vaginal specimens. Conclusions: Vaginal, urine, and endocervical samples showed excellent agreement for diagnosis of TV and are all acceptable specimens for use with the BD Viper™ System in extracted mode. The development of NAATS testing for TV, especially with the potential use of self-collected vaginal swab and urine specimens should greatly facilitate screening for this common STI.